Growth, Trade, and Deindustrialization - Ramaswamy, Ramana (IMF Working Papers; Working Paper, 1998)
This paper shows that deindustrialization is explained primarily by trends internal to the advanced economies. These include the combined effects on manufacturing employment of a relatively faster growth of productivity in manufacturing, the associated relative price changes, and shifts in the structure of demand between manufactures and services. North-South trade explains less than one fifth of deindustrialization in the advanced economies. Moreover, the contribution of North-South trade to deindustrialization has been mainly through its effects in stimulating labor productivity in Northern manufacturing. It has had little enduring effect on total manufacturing output in the advanced economies.